2018
DOI: 10.1589/jpts.30.605
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical fitness and academic achievement among adolescent in South Korea

Abstract: [Purpose] The purpose of this study was to identify the relationship between physical fitness level and academic achievement in middle school students. [Subjects and Methods] A total of 236 students aged 13–15 from three middle schools in D city, South Korea, were selected using a random sampling method. Academic achievement was measured by students’ 2014 fall-semester final exam scores and the level of physical fitness was determined according to the PAPS (Physical Activity Promotion System) score administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…Muscle strength was measured using handgrip strength, wherein participants had their feet attached to the floor and spread appropriately for an upright posture. After holding the dynamometer (TKK-5401, TAKEI, Niigata, Japan), with appropriate adjustments, measurements were taken for the left and right hand—twice—and the mean value was used as the final value [ 19 , 20 ]. Power was measured through a standing long jump, where participants jumped forward from a starting line as far as possible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle strength was measured using handgrip strength, wherein participants had their feet attached to the floor and spread appropriately for an upright posture. After holding the dynamometer (TKK-5401, TAKEI, Niigata, Japan), with appropriate adjustments, measurements were taken for the left and right hand—twice—and the mean value was used as the final value [ 19 , 20 ]. Power was measured through a standing long jump, where participants jumped forward from a starting line as far as possible.…”
Section: Methodsmentioning
confidence: 99%
“…The researcher measured the straight-line distance from the nearest point of contact by any part of the participant’s body to the floor. Measurements were taken twice, and the best measurement record was used [ 19 , 20 ]. Cardiorespiratory fitness was measured using a shuttle run test.…”
Section: Methodsmentioning
confidence: 99%
“…We performed instrumental variable (IV) analyses to investigate the direct effect of each trait on job satisfaction. In addition, since all three traits (neuroticism, education and physical activity) are correlated with each other 11,[29][30][31][32][33] , we investigated whether these traits have causal effect on job satisfaction, once the correlation between them has been controlled for.…”
Section: Introductionmentioning
confidence: 99%
“…Among the countries of Latin America with high rates of obesity are Bahamas (17.3%), Argentina (16.9%), Chile (15.2%), Dominican Republic (15%), and Mexico with 4.8% of the obese population under 19 years [30]. In this regard, it has been shown that physical activity and practicing sports in students facilitate capacities to be able to respond appropriately to tasks [31], improve cognitive functioning [32], and predict better scores on standardized tests for mathematics or sciences [33,34]. Although, proper eating and sleeping habits are desirable [35], it has been found that students living in vulnerable households with low income have a poor quality of diet, which reduces the chances of having a good performance in school due to an inadequate contribution of energy, fatigue, and lack of attention [36,37].…”
Section: Academic Achievement Relation With Healthmentioning
confidence: 99%